The Method of Moral Educatioan According to Ibn Hajar in Bulughul Maram - Suyadi, Didik; Mujahidin, Endin; Hamat, Anung Al- (Tawazun: Jurnal Pendidikan Islam, 2020)
Moral decline in millennial generation is the reason for the importance of instilling moral education. Moral education is one of the foundations and principles upon which Islamic education is based. One mandate of the goal national education is to instill noble character for students. This study aims to determine the method of moral education by Ibn Hajar in the book of Jami’ Bulughul Maram. Data is collected through document which is then analyzed by content analysis technique. The results showed that according to Ibn Hajar two, namely good morals and bad morals. The method of moral teaching according to Ibn Hajar there are eight, namely targhib wa tarhib, question and answer, repetition, global detail, advice, prayer, talk, and analogy. Abstrak Kemerosotan moral pada generasi milenial menjadi alasan pentingnya menanamkan pendidikan moral. Pendidikan akhlak merupakan salah satu landasan dan prinsip yang mendasari pendidikan Islam. Salah satu amanat dari tujuan pendidikan nasional adalah menanamkan akhlak mulia bagi peserta didik. Penelitian ini bertujuan untuk mengetahui metode pendidikan moral menurut Ibnu Hajar dalam kitab Jami ’Bulughul Maram. Data dikumpulkan melalui dokumen yang kemudian dianalisis dengan teknik analisis isi. Hasil penelitian menunjukkan bahwa menurut Ibnu Hajar ada dua, yaitu akhlak baik dan akhlak buruk. Metode pengajaran akhlak menurut Ibnu Hajar ada delapan yaitu targhib wa tarhib, tanya jawab, ulangan, detil global, nasehat, doa, ceramah, dan analogi.